The relationship between gut microbiota and COVID-19 progression: new insights into immunopathogenesis and treatment - Wang, Man; Zhang, Yuan; Li, Chunmei; Chang, Wenguang; Zhang, Lei (Frontiers in Immunology, 2023)
The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has posed a global health crisis. Increasing evidence underlines the key role of competent immune responses in resisting SARS-CoV-2 infection and manifests the disastrous consequence of host immune dysregulation. Elucidating the mechanisms responsible for deregulated host immunity in COVID-19 may provide a theoretical basis for further research on new treatment modalities. Gut microbiota comprises trillions of microorganisms colonizing the human gastrointestinal tract and has a vital role in immune homeostasis and the gut-lung crosstalk. Particularly, SARS-CoV-2 infection can lead to the disruption of gut microbiota equilibrium, a condition called gut dysbiosis. Due to its regulatory effect on host immunity, gut microbiota has recently received considerable attention in the field of SARS-CoV-2 immunopathology. Imbalanced gut microbiota can fuel COVID-19 progression through production of bioactive metabolites, intestinal metabolism, enhancement of the cytokine storm, exaggeration of inflammation, regulation of adaptive immunity and other aspects. In this review, we provide an overview of the alterations in gut microbiota in COVID-19 patients, and their effects on individuals’ susceptibility to viral infection and COVID-19 progression. Moreover, we summarize currently available data on the critical role of the bidirectional regulation between intestinal microbes and host immunity in SARS-CoV-2-induced pathology, and highlight the immunomodulatory mechanisms of gut microbiota contributing to COVID-19 pathogenesis. In addition, we discuss the therapeutic benefits and future perspectives of microbiota-targeted interventions including faecal microbiota transplantation (FMT), bacteriotherapy and traditional Chinese medicine (TCM) in COVID-19 treatment.